Adaptation of the Short Version of Santa Clara Strength of Religious Faith Questionnaire in Türkiye - Turan, Gulcan Bahcecioglu; Ozer, Zulfunaz; Bayrak, Nisa Yavuzer (Springer, 2025)
The present study was conducted to adapt the short version of the Santa Clara Strength of Religious Faith Questionnaire into Turkish and to examine the validity and reliability of the scale. This methodological study was conducted between January and May 2024 with 283 individuals aged 18 and older in Turkey. Data were collected online by using Personal Information Form and the Short Version of the Santa Clara Strength of Religious Faith Questionnaire. It was found that all participants believed in God. According to the study results, item-based content validity index (I-CVI) was between 0.87 and 1.00, and the scale-based content validity index (S-CVI) was found to be 0.98. Factor loadings of the scale items vary between 0.570 and 0.840. Fit indices of the scale were calculated as follows: X-2 = 9.64, df = 4 (p < 0.05), X-2/df = 2.41, RMSEA = 0.071, CFI = 0.99, SRMR = 0.021, TLI = 0.98, RMR = 0.012, AIC = 31.64. The overall Cronbach's alpha value of the scale was 0.860, and the Omega reliability value was 0.866. Short Version of the 5-item Santa Clara Strength of Religious Faith Questionnaire was validated without any changes to the original form. The Turkish version of the Short Version of the Santa Clara Strength of Religious Faith Questionnaire is a valid and reliable instrument for measuring individuals' strength of religious faith.
Keywords: Santra Clara; Religion; Faith; Spirituality; Nursing